2005
DOI: 10.1002/chem.200401257
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Supramolecular Properties of Molecular Clips with Anthracene Sidewalls

Abstract: Novel molecular clips with anthracene sidewalls (1 a-c) were synthesized; they form stable host-guest complexes with a variety of electron-deficient aromatic and quinoid molecules. According to single-crystal structure analyses of clip 1 c and 1,2,4,5-tetracyanobenzene (TCNB) complex 14@1 b, the clips' anthracene sidewalls have to be compressed substantially during the complex formation to provide attractive pi-pi interactions between the aromatic guest molecule and the two anthracene sidewalls in the complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Though 1 is rather rigid, a larger aperture of the bite could be achieved by multiple small‐angle distortions in the structure of the bis‐porphyrin tweezers, which could be affordable with low‐energy costs. Recently, force‐field calculations have shown that compression and expansion of the side‐walls in a molecular clip with anthracene side‐walls are low‐energy processes 22. The energy necessary for the expansion can be compensated by the formation of new bonds in the host–guest complex.…”
Section: Resultsmentioning
confidence: 99%
“…Though 1 is rather rigid, a larger aperture of the bite could be achieved by multiple small‐angle distortions in the structure of the bis‐porphyrin tweezers, which could be affordable with low‐energy costs. Recently, force‐field calculations have shown that compression and expansion of the side‐walls in a molecular clip with anthracene side‐walls are low‐energy processes 22. The energy necessary for the expansion can be compensated by the formation of new bonds in the host–guest complex.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the presence of the peripheral methoxy groups, the electrophilicity of the triketone should be markedly reduced as compared to the parent triptindanetrione, which was found to undergo threefold addition of nucleophiles, such as phenyllithium and methyl-and benzylmagnesium bromide. [5,23,28,31] In the present case, the addition of three veratryl residues to the triketone 15 was carried out by use of 4-veratrylmagnesium bromide, prepared from 4-bromoveratrole (16) ·+ at m/z = 774 and m/z = 912, respectively). Similarly rapid, and highly stereospecific, loss of water is known for other preoriented bridgehead-hydroxylated centropolyindanes and simpler cyclic alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…82 Complexes of clips (65) are weaker than those of clips (66), since 66 have larger van der Waals contact surfaces of the anthracene sidewalls as compared with naphthalene sidewalls of 65. 82 Complexes of clips (65) are weaker than those of clips (66), since 66 have larger van der Waals contact surfaces of the anthracene sidewalls as compared with naphthalene sidewalls of 65.…”
Section: Molecular Clipsmentioning
confidence: 99%